2020
DOI: 10.21597/jist.704240
|View full text |Cite
|
Sign up to set email alerts
|

Some Quality Properties of Vinegar Produced by Traditional Method from Different Species of Blueberries

Abstract: Bu çalışmada, geleneksel yöntemle üç farklı yaban mersini türü ile (Vaccinium corymbosum L., Vaccinium arctostaphylos L. ve Vaccinium uliginosum L.) üretilen sirkelerin bazı fiziksel, kimyasal ve duyusal kalite özelliklerinin belirlenmesi araştırılmıştır. Araştırma sonunda en yüksek; pH (4.11), toplam asitlik (27.5 g L-1), kuru madde (4.8 %), kül (4.5 g L-1), briks (4.91 °Briks), yoğunluk (1.039 g cm-3), iletkenlik (2.51 μS cm-1), toplam antioksidan (141.14 μg troloks eşdeğeri (TE) mL-1) ve toplam fenolik madd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The main components and bioactive compounds of hawthorn vinegar have been revealed in many studies. It has been reported that the total amount of antioxidants in traditional hawthorn vinegar fermentation methods have high phenolic and antioxidant capacities [32]. Additionally, in one study, the fermentation of vinegar increased the number of citric acid and acetic acid compounds [6].…”
Section: Introductionmentioning
confidence: 95%
“…The main components and bioactive compounds of hawthorn vinegar have been revealed in many studies. It has been reported that the total amount of antioxidants in traditional hawthorn vinegar fermentation methods have high phenolic and antioxidant capacities [32]. Additionally, in one study, the fermentation of vinegar increased the number of citric acid and acetic acid compounds [6].…”
Section: Introductionmentioning
confidence: 95%